The Role of Komunitas Guru Belajar (KGB) in Creating Independent Teachers of Islamic Education - Ma’mun, Syukron; Nadia, Syarifatun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study investigates the Komunitas Guru Belajar (KGB) and its role in promoting self-regulated learning among Islamic religious education teachers. It focuses on three key aspects: KGB's proactive measures, its pivotal role in facilitating self-regulated learning, and the factors influencing its effectiveness. Using qualitative methods, we conducted fieldwork and gathered data from primary and secondary sources. Primary sources included interviews with KGB founders, leaders, and teachers, along with instructional materials. Secondary sources encompassed reference books, periodicals, online resources, and related articles. Data analysis followed the Milles and Huberman model, involving data reduction, presentation, and conclusions. The findings highlight KGB Pekalongan's diverse program activities aimed at fostering self-regulated learning among Islamic religious education teachers. Beyond program implementation, KGB serves as a supportive environment, nurturing teachers' professional growth and competencies. It also encourages collaboration among teachers and various communities, enabling collective achievements and aligning career aspirations with individual potentials. Several supportive factors contribute to KGB's success, including the endorsement of self-directed learning by the Indonesian Minister of Education and Culture, support from local governments and official services, collaborations with diverse communities and relevant organizations, and a competent and motivated human resource pool.